A COMPARATIVE ANALYSIS OF CONSUMER BUYING PREFERENCE: TRADITIONAL MENU CARD VS. SMART MENU CARD - Surekha, Shetty; Ali, Shaukat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly changing restaurant industry, smart menu cards are reshaping consumer buying preferences. This study investigates the differences between traditional and smart menu cards and their impact on customer choices in restaurants. Using a mixed-methods approach, the research examines data from a diverse group of diners who have used both types of menus. The results indicate that while traditional menus are valued for their sentimental and familiar aspects, smart menus are favored for their convenience, efficiency, and ability to provide a personalized dining experience. The study also explores how these preferences affect restaurant management and marketing strategies, emphasizing the potential of smart menus to enhance customer engagement and optimize operations. The paper concludes with suggestions for restaurateurs on how to transition to digital menus while preserving the traditional dining experience.